Hermaphrodite Woman. The Rhetoric of Sexuality and Femininity in the Short Stories of A.G. Matoš [the Example of the Short Story Crossroads Flower] - Vuković, Tvrtko; Žužul, Ivana (Poznańskie Studia Slawistyczne, 2014)
The literary work of A.G. Matoš is characterized by a strong interest in femininity and sexuality. The analyses of female’s figures and sexuality in the author’s oeuvre have strived to imbue these concepts with stable meaning. Our thesis is that sexuality and the rhetoric of femininity are generally unreadable and ambiguous, and that their direct, literal interpretations are based on their unconscious exclusion. The example of the short story Cvijet sa raskršća (Crossroads Flower) shows that the rhetoric of femininity works as a drive of the text and its reading, and that the interpretations, trying to calm the ambiguity of that concept, remain blind to the blindness of insight, for what the text sets as a necessary condition of its own reading and understanding.